Press Release and Crises Management " An Analytical Study of Press Releases on the Crisis of Basra " - MAKI KADHIM, SAMAH; MUSTAFA DAKHIL, ALAA (ALBAHITH ALALAMI, 2021)
The press release plays an important role in understanding and recognizing the policy of governments by the public in managing the state, especially in times of crises, as it helps to clarify the position of the government and its decisions.In addition, it is considered as one of the most important tools of communication between the government and its public at the present time. In light of the technical developments and adopting modern mechanisms in transferring of what is issued by the government, the press release has been edited and published electronically; and helps in the success of this transfer speed and knowledge of the reactions of the masses towards the implications,In a crisis like the Basrah crisis in particular, the Iraqi government used the statement a lot as it is the official window that the government overlooks its people ,On the same side, the Public Relationsas a department or office is responsible for issuing these statements provided that the press release is carrying the solutions, conveying the government’s position and decision. Based on this, the issue of this research was to identify the most important contents addressed in the data and to know whether there is coordination and agreement between the issuers and the elements of manifestation adopted by those statements ,Therefore, this study aims to identify the contents of press releases used by Public Relations in editing the government statements on the crisis in Basra. The researcher has used the descriptive approach, which she considered the most appropriate to come up with accurate results and indicators of the study, The researcher also used the content analysis tool, which is one of the most important methods used in descriptive research. The researcher reached a number of results, the most important of which is the lack of public service suffered by the public of Basrah, which they demonstrated for, namely water, electricity, unemployment and the agreement of the vast majority of statements in Tahrir. They agreed to stand by the protests if they were peaceful and non-violent. It also drew attention to the statements to develop solutions to the existing crisis; or to mitigate its sharpness, whether to apply these solutions over a long time, or cost a lot; or they formed a system of solutions that may advance the reality of Basrah service.